Maternal factors associated with immediate low Apgar score in newborn babies at an intermediate hospital in Northern Namibia - Justina Lungameni; Emma Maano Nghitanwa; Laura Uusiku; Abel Karera (AOSIS, 2022)
Background. All newborn infants are required to undergo the Apgar score/assessment immediately after birth and again at five minutes. This vital examination is performed to determine how well the infant is adjusting to the birthing process and the outside environment. Some newborns may have a normal Apgar score, while others may have a low score. The purpose of this study was to identify factors associated with low Apgar scores among newborns at an intermediate hospital in Northern Namibia. Objective. To identify maternal factors associated with an immediate low Apgar score in newborns at an intermediate hospital in Northern Namibia and to examine the association between maternal factors and an immediate low Apgar score. Quantitative, retrospective, descriptive research methodology was employed. A document review checklist was utilized to collect data at Onandjokwe Intermediate Hospital between August 2020 and October 2020. Results. Gravidity (p0.021), parity (p0.029), haemoglobin after the first ante-natal care visit (p0.011), antepartum haemorrhage (APH) (p0.004), membrane status (p0.000), duration of labour (p0.000), type of delivery (p0.000), and caesarean section type and indication (p0.000) were found to be associated with an immediate low Apgar score. Conclusions:  The study identified maternal factors that influence an infant's initial low Apgar score. Strengthen maternal health education regarding gravidity and parity, diet, and recognizing danger signs during pregnancy. In addition, strict monitoring of patients with a partograph, cardiotocography, accurate record keeping, and prompt referral of patients with risk factors is strongly advised.